Hushing Contracts - David A. Hoffman; Erik Lampmann (Washington University Law Review, 2019)
The last few years have brought a renewed appreciation of the costs of nondisclosure agreements that suppress information about sexual wrongdoing. Recently passed bills in a number of states, including New York and California, have attempted to deal with such hush contracts. But such legislation is often incomplete, and many courts and commentators continue to ask if victims of harassment can sign enforceable settlements that conceal serious, potentially metastasizing, social harms. In this Article, we argue that employing the public policy doctrine, courts ought to generally refuse to enforce hush agreements, especially those created by organizations. We restate public policy as a defense which should be concerned with managing externalities, and which expresses a legitimating account of contract law.
Keywords: Contract law; Nondisclosure agreements; Public policy doctrine; Sexual harassment; Sexual misconduct; Sexual assault; Hush contracts; Contract defenses; #MeToo movement